MINI-FOOTBALL AS A MEANS OF COMPREHENSIVE DEVELOPMENT OF UNIVERSITY STUDENTS - Allaev Sherkul Axmuratovich; Mukimjonov Mirziyo (The Conference Hub, 2025)
This article explores the role of mini-football in promoting the comprehensive development of university students. As a fast-paced, accessible team sport, mini-football offers significant physical, psychological, and social benefits. It enhances cardiovascular health, motor coordination, endurance, and muscular strength, while also contributing to stress reduction, motivation, and emotional balance. Moreover, mini-football encourages teamwork, communication, leadership, and discipline—qualities essential for academic success and future professional life. The article examines how mini-football is implemented in university physical education programs and extracurricular activities, with practical examples drawn from Kazan (Volga Region) Federal University (Jizzakh Branch). The findings support the inclusion of mini-football as an effective tool for student wellness and personal growth.
Keywords: mini-football, university students, physical education, student wellness, comprehensive development, teamwork, student motivation, higher education sports.